Isaac Newton : the story of one of the greatest mathematicians who changed our perception of the universe - White, Michael, 1959- (Hyderabad : Orient Longman, 1994)
Describes the life and scientific contributions of the famed English mathematician who changed our perception of the universe.
Includes bibliographical references and index.
Keywords: Newton, Isaac, -- Sir, -- 1642-1727 -- Juvenile literature; Newton, Isaac, -- Sir, -- 1642-1727.; Physics -- History -- Juvenile literature; Physicists -- Great Britain -- Biography -- Juvenile literature; Physicists